Analisis Perbandingan Tingkat Kesehatan Bank Berdasarkan Risk Profile, Good Corporate Governance, Earnings Dan Capital (Rgec)Pada Bank Bumn dan Swasta (Studi Pada Bank BUMN dan Swasta yang Terdaftar di BEI Tahun 2012-2014) - Rahayu, Lilis Sri; , Dr. Zulfikar, SE, M.Si (2016)
Bank Indonesia issued regulation on the rating of commercial banks based on PBI No. 13/1/PBI/2011 using RGEC methods that include these components: Risk profile, Good Corporate Governance (GCG), Earnings and Capital. This research aims to determine the condition of commercial banks are in very healthy condition, healthy condition or quite healthy condition, and comparing the level of health in the state-owned commercial bank with the national private-owned bank foreign exchange. The researcher measured the ratio of the bank using three assessment factors: Risk profile using NPL and LDR ratio, Earnings using ROA and NIM ratio and Capital using CAR ratio. The research was conducted on the four State-Owned Commercial Banks and twenty two National Private-Owned Commercial Bank Foreign Exchange as sample. This study shows that the total overall ratio (NPL, LDR, ROA, NIM, CAR) in the year 2012-2014 to the National Private-Owned Commercial Bank Foreign Exchange higher than the State-Owned Commercial Banks.